STUDENTS’ NEEDS ON A BLENDED ASSESSMENT MODEL WITH SELF-DIRECTED LEARNING FOR BASIC READING - Yulmiati Yulmiati; Rani Autila; Melvina Melvina; Dona Alicia (Universitas PGRI Sumatera Barat, 2026)
This study investigated the needs of students in a blended assessment model oriented towards self-directed learning for Basic Reading in higher education. The data were collected through a questionnaire for 55 students who took the Basic Reading subject. The researcher employed a random sampling technique to select samples from a private university in Padang City, West Sumatra, Indonesia. The questionnaire was distributed through a WhatsApp Group. The data from the questionnaire were analyzed quantitatively using descriptive statistics analysis. The results indicated that students highly need a blended assessment model for Basic Reading, presented in a blended learning format, to promote their self-directed learning. They need to implement an authentic blended assessment model oriented toward self-directed learning in the Basic Reading subject, as it helps students become more independent.